Correlation between hyperbilirubinemia in term infants and developmental delay in 2-4 year-old children - Rocky Wilar; Nurhayati Masloman; Hesti Lestari; William Stephenson Tjeng (Paediatrica Indonesiana, 2010)
Background Up to 50 percent of term newborns have clinical jaundice during the first week of life. Many infants with bilirubin encephalopathy were asymptomatic, but they show neurodevelopmental delay few years later. Toxic effect occurs if unbound unconjugated bilirubin penetrates blood brain barrier and causes neuronal death.Objective To investigate the relationship between moderate hyperbilirubinemia in tenn infants and developmental delay in 2- 4 year-old children.Methods A retrospective cohort study was performed usingmedical record of infants born between 2006-2007 in Division of Neonatology Prof. R.D. Kandoll General Hospital, Manado. Data from the medical record consisted of weeks of gestation, birth weight, Apgar scores, diagnosis of sepsis, congenital anomalies. Tenn infants with appropriate weight for gestational age were visited at their home to undergo developmental screening by Denver II and Vineland Social Maturity Scale test.Results Fifty one children enrolled in this study (26 children with hyperbilirubinemia and 25 without  hyperbilirubinemia) consisted of 27 boys and 24 girls. Most children were 24 - 29 months old (24/51). The results of Vineland Social Maturity Scale test showed 14 children had delayed social maturation (10 Mth history of  hyperbilirubinemia). Denver II screening found 11 children had delayed language skill (10 Mth history of hyperbilirubinemia), 1 child Mth hyperbilirubinemia had delayed fine motoric and language skill.Conclusions T here is a relationship between moderate hyperbilirubinemia in tenn infants and developmental delay in 2 - 4 year old children.